Supply chain risk mitigation through visibility and collaboration for SMEs in the South African manufacturing enviroment - Cipolat, Alberto C (My University, 2016)
Risk is defined as the probability of a variance in an expected outcome. Two concepts that SMEs (and any size organisation) can use in order to manage risk in the supply chain are those of visibility and collaboration. These two concepts if managed correctly have the opportunity to mitigate risk and enhance competitiveness. This research paper undertook the study of the supply chains of six SMEs, through the interview of their owner/managers, operating in the South African manufacturing environment. These interviews were conducted with the owner/managers as they were deemed the most knowledgeable person/people in the organisation. The results from the data collected showed that the concepts of visibility and collaboration are used in the operations of these businesses, but only informally. Nonetheless, it was also found to an intrinsic part of the decision making and planning processes and can be used on the demand side of the supply chain to manage and mitigate risk.